Magnetic resonance spectroscopy quality assessment at CUBIC and application to the study of the cerebellar deep nuclei in children with fetal alcohol spectrum disorder - Du Plessis, Lindie (Department of Human Biology, 2015)
Includes bibliographical references (leaves 73-79).